International Children's Rights Instruments - Hanson, Karl,; Klep, Katrien,; Liefaard, Ton,; Opoka, Lucy,; Patrizi, Elena,; Ruggiero, Roberta, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
This collection is an essential supplement to the recent academic handbooks on children's rights studies and international children's rights law. Over the years, the international legal framework on children's rights has evolved into a complex system, which includes United Nations treaties and resolutions, regional human rights instruments, such as treaties, recommendations, resolutions, and guidelines, both of private and public international law. For students, researchers, and professionals, navigating this complex social and legal landscape can be challenging. A comprehensive and easily accessible overview of these legal sources is crucial for effectively understanding and promoting children's rights. Edited by leading experts in the field, this book is meticulously designed to provide exactly that, making it an invaluable resource for anyone dedicated to the protection and promotion of children's rights. See Less